Genetic Severity Score predicts clinical phenotype in NF2. Issue 10 (28th August 2017) - Halliday, Dorothy; Emmanouil, Beatrice; Pretorius, Pieter; MacKeith, Samuel; Painter, Sally; Tomkins, Helen; Evans, D Gareth; Parry, Allyson
Abstract : ​Background: The clinical severity of disease in neurofibromatosis type 2 (NF2) is variable. Patients affected with a constitutional truncating NF2 mutation have severe disease, while missense mutations or mosaic mutations present with a milder attenuated phenotype. Genotype-derived natural history data are important to inform discussions on prognosis and management. Methods: We have assessed NF2 clinical phenotype in 142 patients in relation to the UK NF2 Genetic Severity Score to validate its use as a clinical and research tool. Results: The Genetic Severity Score showed significant correlations across 10 measures, including mean age at diagnosis, proportion of patients with bilateral vestibular schwannomas, presence of intracranial meningioma, spinal meningioma and spinal schwannoma, NF2 eye features, hearing grade, age at first radiotherapy, age at first surgery and age starting bevacizumab. In addition there was moderate but significant correlation with age at loss of useful hearing, and weak but significant correlations for mean age at death, quality of life, last optimum Speech Discrimination Score and total number of major interventions. Patients with severe disease presented at a younger age had a higher disease burden and greater requirement of intervention than patients with mild and moderate disease. Conclusions: This study validates the UK NF2 Genetic Severity Score to stratify patients with NF2 for both clinical use and natural history studies.